IL-15 as a potential target in leukemia - Xiong Y (Dove Medical Press, 2015)
Yu Xiong,1,2 Danièle Bensoussan,1,3 Véronique Decot1,3 1Cell Therapy Department, University Hospital of Nancy, Vandoeuvre les Nancy, France; 2Institute of Hepatobiliary Diseases, Transplant Center, Wuhan University, Hubei Key Laboratory of Medical Technology on Transplantation, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 3UMR CNRS UL 7365, Lorraine University, Vandoeuvre les Nancy, France Abstract: Leukemia, one of the most aggressive hematopoietic malignancies, is characterized by excessive proliferation, survival, and impaired differentiation of hematopoietic stem cells. Interleukin 15, a proinflammatory cytokine, induces proliferation and promotes cell survival of human T and B lymphocytes, as well as natural killer cells. However, it may also play a detrimental role in the onset of leukemia. This review provided an overview of the aberrant expression of Interleukin 15 and its role in the development and progression of this hematological malignancy. Also, we critically explored the potential therapeutic opportunities involved in targeting the disruption of interleukin-15 signaling as well as in interleukin-15-mediated enhancement of antitumor immunity. Keywords: leukemia, interleukin-15, immunotherapy